2019
DOI: 10.1097/bor.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for rheumatoid arthritis treatment

Abstract: 1. Purpose of review: To provide an overview of recent articles discussing patient preferences for rheumatoid arthritis treatment. 2. Recent findings: Recent studies examined patient preferences for rheumatoid arthritis (RA) treatment in several populations, finding that most participants were willing to accept certain risks of adverse effects to gain potential benefits. Perspectives regarding cannabis were studied, with patients describing medical marijuana as an alternative therapy to be used with prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Studies conducted among individuals with RA showed the preference for subcutaneous injections in comparison to intravenous infusions and tendency to select ready to use drug delivery systems, with a high preference for pen autoinjectors [ 13 17 ]. Moreover, the risk of side effects associated with treatment method was not neglectable [ 18 ]. Currently, MTX is available in Poland in two forms: oral pills and subcutaneous prefilled syringes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted among individuals with RA showed the preference for subcutaneous injections in comparison to intravenous infusions and tendency to select ready to use drug delivery systems, with a high preference for pen autoinjectors [ 13 17 ]. Moreover, the risk of side effects associated with treatment method was not neglectable [ 18 ]. Currently, MTX is available in Poland in two forms: oral pills and subcutaneous prefilled syringes.…”
Section: Discussionmentioning
confidence: 99%
“…Matching treatment to patient preferences has been shown to improve adherence 5 6. Previous studies have shown that patient preferences for RA treatment vary widely and often differ from those of clinicians 7–11. Therefore, it is important that clinicians and patients make treatment decisions together using the best available evidence and accounting for patient preferences 12.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted among individuals with RA showed the preference for subcutaneous injections in comparison to intravenous infusions and tendency to select ready to use drug delivery systems, with a high preference for pen autoinjectors [ [13][14][15][16][17]. Moreover, the risk of side effects associated with treatment method was not neglectable [ 18 ]. Currently, MTX is available in Poland in two forms: oral pills and subcutaneous prefilled syringes.…”
Section: Discussionmentioning
confidence: 99%